THE MICROBIOLOGICAL QUALITY OF RAW MILK DETERMINED ACCORDING TO THE MILKING SYSTEMS USED - Victoria Codău (Furcea); Marian Mihaiu; Vlad Luca; Daiana-Alexandra Platon; Maria Crăciun (Agricultura)
This study examined the microbiological parameters of raw milk according to milking systems. The raw material milk was collected from 10 holdings with different forms of ownership, with different technical equipment and different milking systems. The microbiological parameters of milk from the period April 2021-March 2022 were analyzed, respectively the determination of NTG/ml in milk at 30°C and NCS by the electronic fluoro-opto method. According to EC Regulation 853/2004 for raw milk NTG at 30°C (per ml) ≤ 100,000, it follows that of the 10 holdings included in the research, 14 values of the geometric mean over a period of two months do not fall within the limit allowed according to the CE standard, and for NCS (per ml) ≤ 400,000, it follows that out of the 10 holdings included in the research, 7 values of the geometric mean for a period of three months do not fall within the limit allowed according to the CE standard.